In Defense of Posthuman Ethics: Contributions from Braidotti, Sloterdijk, and Marchesini - Piedra-Alegría, Jonathan (2024)
This philosophical essay, framed within the qualitative and documentary paradigm, embarks on an exploration of the concept of posthumanism, guided by the contributions of three prominent thinkers: Rosi Braidotti, Peter Sloterdijk, and Roberto Marchesini. Using hermeneutics as an interpretative methodology, the essay addresses the written texts of these authors to unravel and comprehend their ideas. Posthumanism, as a philosophical framework, challenges the boundaries of classical humanism, rethinking the position of the human being in relation to nature and technology, alongside other significant entities. In this context, connections and interactions with the environment, technological systems, as well as other living beings become fundamental in the construction of identity and human experience. Through an analysis of the works of Braidotti, Sloterdijk, and Marchesini, the essay reveals how posthumanism acts as an incisive critique of anthropocentrism, as well as traditional humanisms, offering a renewed and critical perspective on ethics and the human condition in our contemporary era.